Synthesis and Study of Palladium(II) and Platinum(II) Complexes Supported by a Common "Wingtip" N‐Heterocyclic Carbene. Issue 38 (16th October 2018) - Dinda, Joydev; Jhulki, Lalmohan; Kisan, Hemanta K.; Mahapatra, Pradip K.; Isab, Anvarhusein A.; Bielawski, Christopher W.
Abstract: Two annulated imidazolium salts, 2‐(phenyl)imidazo[1, 5‐ a ]pyridin‐4‐ylium hexafluorophosphate1⋅ H(PF6 ) and 1‐methyl‐2‐(phenyl)imidazo[1, 5‐ a ]pyridin‐4‐ylium hexafluorophosphate2⋅ H(PF6 ), were synthesized via formylative cyclization of the corresponding Schiff bases followed by anion metathesis with KPF6 . Independently treating1⋅ H(PF6 ) or2⋅ H(PF6 ) with silver oxide and then palladium chloride in acetonitrile led to the formation of the complexes [Pd(1 )2 Cl(CH3 CN)]PF6 (1 a ) and [Pd(2 )2 Cl(CH3 CN)]PF6 (2 a), respectively. Likewise, [Pt(1 )2 Cl(CH3 CN)]PF6 (1 b) and [Pt(2 )2 Cl(CH3 CN)]PF6 (2 b) were synthesized using similar transmetallation chemistry. The complexes were characterized using various spectroscopic techniques and the solid state structures of1‐ H(PF6 ) as well as2 a were elucidated using X‐ray diffraction analyses. A series of DFT calculations were also performed to gain further insight into the respective structures of the complexes. Complexes1 a and2 a were found to facilitate Suzuki coupling reactions under relatively mild conditions. Abstract : The synthesis, structural characterization and catalytic activity displayed by novel Pd(II) complexes supported by an annelated NHC are highlighted. DFT calculations were performed to gain a deeper understanding of the bonding and a natural bond orbital analysis was conducted to elucidate the electronic structures of the complexes.